(3cfR GdObGFb aj aQhY GdMfajIs - (3GdnqfnSaj, CHh GdHQcGJ, MGaX GdOjf, YHO Gddg Hf CMeO Hf eMehO, (B710 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CYR GdYde aj GdCYUGQ hCYdG MRHg aj GdCeUGQ bGd CHh GdHQcGJ YHO Gddg Hf CMeO Hf eMehO GdfSaj deG QCjJ Gdgee eGjdI Edi GdeNJUQGJ hGdWHGY QGZHI Yf GdeWhdGJ CQOJ Gf CdNU GdhGaj HPcQ eG Ye hbhYg hcKQ hLhOg hSejJg HcfR GdObGFbs
(3BNQgG (B:s
(3hjSbW ef Ohfg hddCNhGJ dCH hCe cHfGJ GdUdH YfO YOegf hdC cHfGJ GdGHf eY GdUdHjI hYUHgf CNhJgf hGdHfJ GdGHf cPdc hdcd hGMO ef s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 67s
(3eYLe GdeDdajf (B2 / 228s
(3cTa GdXfhf (B2 / 1515s
(3gOjI GdYGQajf (B1 / 464s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs